Nationalistic education and its colourful role in intergroup prejudice reduction: lessons from Albania. Issue 3 (3rd July 2021) - Peshkopia, Ridvan; Giakoumis, Konstantinos
ABSTRACT: Contributors to the education-as-enlightenment approach maintain that education helps to create less prejudicial individuals. This conclusion, emanating mainly from data collected in western democracies that apply multicultural education might not apply to countries where education's primary goal is the establishment of a sense of national unity and belonging. On the one hand, nationalist education could reduce prejudices against groups not targeted by the ethnonationalist narrative – e.g. through positive comments about them or by not mentioning them at all. On the other hand, education might produce more prejudice towards groups targeted as the hostile Other through a nation-building narrative. We test this argument with a simple random sample of a cellphone public opinion survey collected in Albania in 2015. By framing our analysis inside the intergroup contact theory, we build two sets of models, the first explaining respondents' prejudice levels towards Greeks and the second explaining respondents' prejudice levels towards homosexuals. We found that more education predicted respondents' higher prejudice levels towards Greeks, a group targeted by the Albanian ethnonationalist narrative as the hostile Other, whereas it did not significantly affect prejudices towards homosexuals.